miR-155-5p drives coordinated tumor and macrophage reprogramming across multiple cancer entities - Theresa Kordaß; Ann-Katrin Schlosser; Marijan Czygan; Luisa Vieira Codeco Marques; Melisa Wartusch; Eric Nerenz; Vincencia Stefanie Muliawan; Stephan Kersting; Wolfram Osen; Stefan B. Eichmüller (BMC Medicine, 2026)
Abstract Background T cell-based immunotherapies have improved cancer treatment, however their efficacy is frequently limited by tumor-intrinsic resistance mechanisms and by the immune suppressive tumor microenvironment, counteracting tumor specific immune responses through impaired antigen presentation and the accumulation of M2-like tumor-associated macrophages. MicroRNAs have emerged as regulators of tumor cell – immune cell interactions, yet the miRNAs’ capacity to coordinate anti-tumor effects across different cell types is poorly understood. This study aimed to investigate whether miR-155-5p and miR-3535 represent regulators capable of driving coordinated functional reprogramming of both, tumor cells and macrophages. Methods Human tumor cell lines of various cancer entities were transfected with miR-155-5p or miR-3535 and the resulting effects on immune checkpoint molecule expression and tumor cell proliferation were assessed on transcriptional and functional level. Similarly, human PBMC-derived M2 polarized macrophages were transfected with the same microRNAs, followed by analysis of the cytokine secretion patterns and by transcriptomic profiling to evaluate the macrophage polarization states and the immune-regulatory pathways involved. Transcription factor activity and pathway enrichment analyses were performed to identify the regulatory mechanisms affected. Results Both miR-155-5p and miR-3535 reduced expression of the immune checkpoint molecule CD73 (NT5E) in tumor cells, while miR-155-5p additionally suppressed PD-L1 (CD274) expression. At the same time, both microRNAs reprogrammed M2-like macrophages toward a pro-inflammatory M1-like phenotype, characterized by increased TNFα and CXCL10 secretion and the induction of M1-associated gene expression. Transcriptomic analysis revealed activation of STAT1/IRF-driven inflammatory pathways and a reduced activity of ZNF703, representing a transcriptional hub associated with M2 macrophage infiltration and poor prognosis. Both microRNAs increased TAP1 expression, suggesting enhanced antigen-processing capacity. Furthermore, miR-155-5p and miR-3535 exerted anti-proliferative effects across cell lines of various tumor entities. Conclusions miR-155-5p and miR-3535 modulate tumor-intrinsic immune checkpoint expression and functional macrophage polarization in a coordinated way, linking tumor cell plasticity to neutralization of the immunosuppressive tumor environment. These findings highlight the potential of coordinated microRNA-mediated regulation via different cell types to overcome immune resistance mechanisms in tumors and support further investigation of microRNA-based strategies in cancer immunotherapy.